El sistema nacional de desarrollo curricular y las rutas del aprendizaje - Cruzalegui Delgado, Magaly (2013)
In the following article, the author explores many education-relatedaspects, such as: Curriculum Framework importance which have toanswer the question: what do the students must learn through theirschool stage?, improvement Maps which have to answer the question:what must to look and according to what criteria? And finally, the wellknownand diffused Learning Routes which show us the way of How toachieve those learnings.